Students Metacognition Strategies and Learning Achievement in Mathematical Economics - Farida Styaningrum (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2019)
The purpose of this study to develop metacognition strategies students in optimizing learning achievement in mathematical economics. The applied a qualitative method consisting of data reduction, data display, and conclusions. Research informants were all students in mathematical economics courses totaling 23 students. Data collection techniques were by observation, interview and documentation. The findings showed that, metacognition approach makes students easier to overcome mathematical problems in economics. In addition, several obstacles occured in the process of metacognition are difficulties in concentration, lack of confidence, fear of trying and lack of reference books owned. Therefore, the suggested strategies to develop the students metacognition are more practice working on the problem, enhancing students confidence, increase motivation, and having a reference book.